Uma arquitetura de comunicação oportunística - Moschetto, Danilo Augusto (2010)
Mobile computing devices often present high processing power and include several wireless network interfaces. 4G networks promise to provide a unified IP based infrastructure with QoS and security support for the communications using such devices. Transmission delays, and network disruptions, however, are often common when considering the current transmissions of mobile users. This work presents a software communications architecture which is tolerant to transmission delays and intermittent connectivity by exploring a hop-by-hop forwarding mode in DTNs. The proposed architecture is organized as a set of functional layers, which allow the use of different forwarding policies and network technologies. By providing the forwarding of objects, named bundles, an unlimited number of high level communication applications can be implemented on top of the architecture. Security aspects concerning the proper identification of users and transmission bundles, as well as the confidentiality and authentication of the received information are considered in the project of the developed architecture. Log keeping of the bundle forwarding activities performed by the architecture, including the interactions among users and the data passing operations, may be further investigated for use in different context aware forwarding and social organization algorithms. A partial implementation of the developed architecture was made and the results demonstrate the viability of its operation.